Պատեր և պարիսպներ․ մասնավորի ու հանրայինի միջև սահմանները Կիլիկյան Հայաստանի քաղաքային միջավայրում - Գևորգյան, Զոհրաբ
When in the 12th century King Levon I (as prince, Levon II, 1187–1198, as king, 1198–1219) united the state with a part of the northeastern shores of the Mediterranean, Cilician Armenia quickly became involved in the most developed financial and economic relations of the time. The accessibility of documenting on paper changed the way people treated and used their private property. While in earlier centuries only people of higher social strata could document their property using parchment, the wide circulation of paper and the increase in its production made it possible to document property for different classes, including both men and women. The capital and private property are components characterizing medieval culture of everyday life. The types and transformations of private properties are mentioned in historical sources, particularly in the Law Codes of Mkhitar Gosh and Smbat Constable. There are numerous laws and rich evidence in their works on the division of different types of properties (marital property etc.). The documents prepared in Cilician Armenia by notarial agents, mainly from Genoa and Venice, are also important and unique sources for this study. Когда в XII веке король Киликийской Армении Левон I (в качестве князя Левона II – 1187-1198, как король – 1198-1219) объединил государство с частью северо-восточного побережья Средиземного моря, Киликийская Армения быстро вовлеклась в наиболее развитые финансово-экономические отношения того времени. Возможность документировать частный капитал на бумаге изменила способы обращения частной собственности и ее использования. Если в прежние века только люди высших социальных слоев могли документировать свою собственность на пергамене, то широкое распространение бумаги и увеличение объемов ее производства позволило документировать собственность разным сословиям – как мужчинам, так и женщинам. Капитал и частная собственность – это составляющие средневековой культуры повседневности. Виды частной собственности и ее преобразований в Киликийской Армении отражены в исторических источниках, в частности, в уложениях Мхитара Гоша и Смбата Гундстабля. В их кодексах имеется множество законов и свидетельств о разделе различных видов имущества (имуще- ства супругов и т.д.). Много свидетельств содержится в документах, составленных в Киликийской Армении нотариальными агентами, в основном из Генуи и Венеции: это уникальные источники по интересующему нас вопросу.
Keywords: Պատմություն